Method for Obtaining Isothermal Diagrams of the Liquid - Vapor Equilibrium for the System as Dimethyl Zinc - Dimethyl Telluride - Gerasymchuk, Serhiy; Poliuzhyn, Ihor; Serheyev, Valentyn; Hnativ, Tetiana (Видавництво Львівської політехніки, 2023)
За отриманими експериментальними температурними залежностями тиску насиченої пари розчинів диметилцинк – диметилтелурид з вмістом диметилцинку 50,0 та 70,32 % (мольн.) зроблено ізотермічні перерізи (280, 290, 300, 310 та 320 К ). На основі обмеженого набору експе¬риментальних даних для рівноваги “рідина–пара” проведено розрахунок складу пари за рівнянням Дюгема – Маргулеса, а також парціальних тисків та коефіцієнту розподілу системи диметилцинк – диметилтелурид.

According to the obtained experimental temperature dependences of the saturated vapor pressure on dimethylzinc – dimethyltelluride solutions with dimethylzinc content of 50.0 and 70.32 mol. %, isothermal sections (280, 290, 300, 310, and 320 K) were made. For the dimethylzinc – dimethyltelluride system based on a limited set of experimental data for the “liquid-vapor” equilibrium, the vapor composition was calculated according to the Duhem – Margules equation, as well as the partial pressures and the distribution coefficient.
Метод отримання ізотермічних діаграм рівноваги рідина–пара системи диметил цинк–диметил телурид
Keywords: діаграми стану; рівноваги рідина–пара; диметилцинк–диметилтелурид; тиск пари; diagrams of state; liquid-vapor equilibria; dimethyl zinc – dimethyl telluride; vapor pressure